Sistem Informasi Geografis Pemetaan Reklame Berbasis Web - Tamara Putri; Samsudin Samsudin; Septiana Dewi Andriana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Licensing of billboards is managed by a government agency, namely the Medan City One Stop Integrated Service and Investment Service (DPMPTSP) in the fields of Licensing, Spatial Planning and Development. This study discusses the problems that occur in the Medan City DPMPTSP regarding mapping and monitoring billboard licensing by utilizing Leaflet JS technology as a medium for integrating maps into the web. The system is equipped with a route feature closest to the billboard location and is equipped with a mapping and a list of road locations that are justified and not allowed for advertising. This study uses Quantum GIS to convert shp files into GeoJSON format and Leaflet JS for map visualization. The system created can make it easier for DPMPTSP to manage and find out the status of billboards quickly and accurately and can provide information related to licensing the installation of billboards to the general public.